A prospective video-based analysis of injury situations in elite male football - Arnason, A.; Tenga, A.; Engebretsen, L.; Bahr, R. (The American Journal of Sports Medicine, 2004)
Background: The mechanisms for football injuries are largely unknown. Aim: To describe the characteristics of injury situations in elite male football using a video-based method called football incident analysis. Study Design: Prospective cohort study. Methods: During the 1999 season, videotapes from 52 matches in the Icelandic elite football league were reviewed. Incidents (N = 95) were recorded when the match was interrupted by the referee because of a suspected injury. Team physical therapists recorded injuries prospectively (N = 28 time-loss injuries). Results: Duels caused 84 of the incidents, mostly tackling duels (n = 54). The exposed player`s attention appeared to be focused away from the opponent in 93% of the cases. The 3 main mechanisms observed were (1) breakdown attacks, tackling from the side or the front, attention focused on the ball (24%); (2) defensive tackling duels, attention focused on the ball or low ball control (20%); and (3) heading duels, attention focused on the ball in the air (13%). Conclusion: Most incidents and injuries occurred during breakdown attacks and when a player was involved in tackling duels. Player attention appeared to be focused mainly on the ball, not on the opponent challenging him to gain ball possession.